A COMPARATIVE STUDY OF GOVERNMENT AND PRIVATE SECONDARY SCHOOLS IN IMPHAL EAST DISTRICT, MANIPUR - Moirangthem kunjaraj singh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current analysis directed to measure the influence of infrastructural accommodations on the academic achievement. This study uses the observation method. It has focuses toward the infrastructure facilities and relating student outcome. The infrastructure facilities are fully relation with student of higher qualities and change of the motivation. The public secondary schools sometime poor in infrastructural facilities and lower rate of outcome on another hand the private secondary schools are properly maintainer and good infrastructure facilities, proper arrangement. In Manipur context the public school facilities student motivation has decrease. While private secondary school infrastructures are surficial for student than any competitive exam are higher achievements and job priorities for further life. The quality of student are depend of their building, classroom design, medical facilities, library, teaching aids, computer facilities, transportation facilities, class-size, density of student in class, colour of inside &outside, classroom temperature, number of windows in one class and fitting design, length and breadth of class, sport facilities, and student rest room. All facilities are compulsory for high qualities of student outcome.